Relationship of Nocturnal Sleep Dysfunction and Pain Subtypes in Parkinson's Disease. Issue 1 (8th November 2018) - Martinez‐Martin, Pablo; Rizos, Alexandra M.; Wetmore, John B.; Antonini, Angelo; Odin, Per; Pal, Suvankar; Sophia, Rani; Carroll, Camille; Martino, Davide; Falup‐Pecurariu, Cristian; Kessel, Belinda; Andrews, Thomasin; et al.
Abstract: Background: Little research has been conducted regarding the relationship between sleep disorders and different pain types in Parkinson's disease (PD). Objective: To explore the influence of the various pain subtypes experienced by PD patients on sleep. Methods: Three hundred consecutive PD patients were assessed with the PD Sleep Scale‐Version 2 (PDSS‐2), King's PD Pain Scale (KPPS), King's PD Pain Questionnaire (KPPQ), Visual Analog Scales for Pain (VAS‐Pain), and Hospital Anxiety and Depression Scale. Results: According to the PDSS‐2, 99.3% of our sample suffered from at least one sleep issue. Those who reported experiencing any modality of pain suffered significantly more from sleep disorders than those who did not (all, P  < 0.003). The PDSS‐2 showed moderate‐to‐high correlations with the KPPS (rS  = 0.57), KPPQ (0.57), and VAS‐Pain (0.35). When PDSS‐2 items 10 to 12 (pain‐related) were excluded, the correlation values decreased to 0.50, 0.51, and 0.28, respectively, while these items showed moderate‐to‐high correlations with KPPS (0.56), KPPQ (0.54), and VAS‐Pain (0.42). Among the variables analyzed, multiple linear regression models suggested that KPPS and KPPQ were the most relevant predictors of sleep disorders (as per the PDSS‐2), although following exclusion of PDSS‐2 pain items, depression was the relevant predictor. Depression and anxiety were the most relevant predictors in the analysis involving the VAS‐Pain. Regression analysis, considering only the KPPS domains, showed that nocturnal and musculoskeletal pains were the best predictors of overall nocturnal sleep disorder. Conclusions: Pain showed a moderate association with nocturnal sleep dysfunction in PD. Some pain subtypes had a greater effect on sleep than others.